The Use of Educandy Media on Learning English in the Covid 19 Pandemic Era - Anggita Dwi Saputri; Anita Rachmawati Putri; Gina Aufa Yusuf Sabilla; Triwulan Triwulan; Susilawati Susilawati (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2023)
The Corona Virus (Covid 19) which began to hit this country in early 2020 not only had an impact on health, but also in terms of the economy and even education. Students are required to take online learning. Changes in the system of learning activities from face to face to online are considered boring for students. The process of learning English which is carried out online is considered less effective and makes student learning outcomes decrease so that interesting media are needed to be able to motivate and improve student learning outcomes. For this reason, researchers apply Educandy as an alternative to game-based learning that is not boring. Educandy is a website-based application that has the slogan